THEORY AND PRACTICE OF APPLICATION OF MECHANISMS OF DIGITAL ECONOMY IN BANKS - Norov Akmal Ruzimamatovich (International Journal of Innovations in Engineering Research and Technology, 2021)
The article analyzes the theoretical and practical significance ofthe relevance of the use of innovative technologies in banking services, and also describes measures to develop a digital economy in this area.Based on the analysis, a number of positive aspects of bank lending were studied, including thepositive impact on the countrys GDP and employment growth, as well as recommendations on the development mechanisms of the digital economy in the banking sector based on international experience.